2012
DOI: 10.1177/0095327x11428785
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms among US Military Spouses during Deployment

Abstract: Using the Broaden-and-Build Theory of Positive Emotions, the relationships among stress, positivity, and depressive symptoms were examined in a sample of military spouses during deployment ( N = 367). Over one-third of the spouses reported moderately severe levels of depressive symptoms. After controlling for demographic and deployment variables, stress had a positive association with depressive symptoms (β = .59, p < .001), while positivity had a negative association (β = −.39, p < .001). Positivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…Another survey of 346 Army spouses living with soldiers assigned to installations in Europe found that a spouse's experience of deployment separations (whether it was stressful, put a strain on the family, hurt the stability of the marriage, caused worry about the effect on the children) was predictive of his or her physical and psychological well-being, marital satisfaction, and satisfaction with Army life (Burrell et al, 2006). Yet another small survey of Army spouses, this time 367 spouses in the United States whose soldiers were deployed, found higher levels of positivity and lower levels of stress and depressive symptoms among commis-sioned officers' wives and those with more deployment experience (Faulk et al, 2012). A survey of 34,381 Air Force active duty personnel found that "unit relationship quality, leadership effectiveness, and tangible social support from community memberswere positively and significantly related to members' reports of spousal ability to adjust to Air Force family demands" (Spera, 2009).…”
Section: Spouse's Well-beingmentioning
confidence: 99%
“…Another survey of 346 Army spouses living with soldiers assigned to installations in Europe found that a spouse's experience of deployment separations (whether it was stressful, put a strain on the family, hurt the stability of the marriage, caused worry about the effect on the children) was predictive of his or her physical and psychological well-being, marital satisfaction, and satisfaction with Army life (Burrell et al, 2006). Yet another small survey of Army spouses, this time 367 spouses in the United States whose soldiers were deployed, found higher levels of positivity and lower levels of stress and depressive symptoms among commis-sioned officers' wives and those with more deployment experience (Faulk et al, 2012). A survey of 34,381 Air Force active duty personnel found that "unit relationship quality, leadership effectiveness, and tangible social support from community memberswere positively and significantly related to members' reports of spousal ability to adjust to Air Force family demands" (Spera, 2009).…”
Section: Spouse's Well-beingmentioning
confidence: 99%
“…Although previous works in this field have studied a variety of highly stressed populations, including college students (Fredrickson, Tugade, Waugh, & Larkin, ), public school teachers (Steinhardt et al, ), doctors (Newbury‐Birch & Kamali, ) and military spouses (Faulk, Gloria, Steinhardt, & Cance, ), there is a lack of research toward a particularly high‐stressed population—namely postdoctoral research fellows (postdocs). Postdocs, ironically, are an overlooked and understudied population.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is presented in this study based on the study background, has this default that general positive affectivity like happiness and job-related positive affect play mediating role in the relationship between meaning and spirituality at work and job satisfaction that in addition to the cognitive charge it has job focused affective charge (a particular kind of job-specific positive affect) (Duggleby et al, 2009;Wicker, 2011;Warr & Inceoglu, 2012;Faulk et al, 2012). This part of the prediction of spirituality based affective spillover approach is supported based on two models that have been examined in this relationship in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the previous studies show that there was a positive relationship between positive affect and job satisfaction (Judge & Ilies, 2004;Fredrickson, 2009;Faulk et al, 2012), and between happiness and job satisfaction (Albano, 2009;Wang & Yi, 2011;De Kok, 2013;Warr, 2013). On the other side, meaning and spirituality from affective dimension by providing joy, happiness and positive affect can enhance an individual's sense of job satisfaction (Ho, 2011;Steger et al, 2012).…”
Section: The Role Of Meaning and Spirituality In Job Satisfactionmentioning
confidence: 98%
See 1 more Smart Citation